Analisis Kelayakan Bisnis UMKM Pada Aspek Pemasaran - Kade Dianto; Dwi Andika Saputra (RESWARA: Jurnal Riset Ilmu Teknik, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening national economic resilience, particularly in developing countries. However, many MSMEs fail to sustain their business growth due to weak marketing feasibility analysis. This study aims to analyze the business feasibility of MSMEs from a marketing perspective by examining market potential, marketing strategies, consumer behavior, and competitive positioning. The research adopts a qualitative descriptive approach using secondary data derived from previous feasibility studies and relevant academic literature. Data were analyzed through content analysis to identify key indicators of marketing feasibility commonly applied in MSME studies. The results indicate that marketing feasibility is strongly influenced by market segmentation accuracy, product differentiation, pricing strategies, and the utilization of digital marketing channels. Several studies reveal that MSMEs with structured marketing analysis demonstrate higher sustainability and competitiveness. Conversely, limited marketing knowledge and inadequate market research often lead to suboptimal business decisions. This study concludes that marketing feasibility analysis is a critical determinant of MSME business viability and long-term sustainability. The findings contribute theoretically by strengthening the marketing feasibility framework for MSMEs and practically by providing insights for entrepreneurs and policymakers to enhance MSME marketing performance.